Reproducing the Indigenous: John Møller’s Studio Portraits of Greenlanders in Context - Høvik, Ingeborg (Acta Borealia, 2016)
Manuscript. Published version available at http://dx.doi.org/10.1080/08003831.2016.1238175 Between 1889 and 1922, John Møller (1867–1935), the first professional Greenlandic photographer, produced more than 3000 glass plate negatives documenting life in Western Greenland around the turn of the twentieth century. Rooted in an internal understanding of self, Møller’s photographs played an important part in the formation of a contemporary image of Greenlandic indigenous identity. At the same time, Møller’s photographic practice was arguably entangled in and delimited by a historical reality that was structured by colonial relations of power. This paper examines the social and art- historical contexts of Møller’s work, focusing in particular on a selection of his formal studio portraits. My reading of these portraits suggests a case in which conflicting impulses coincide. On the one hand, Møller produced images that played out the “ethnographic convention”, a European form of representation dating back to the sixteenth century used for the documentation of non-Western indigenous peoples as specimens. However, in acting out that convention, Møller’s photographs hint at a subtle, progressive building-up of identity that reclaimed images of Greenlanders for themselves, and turned an originally negative, external image of indigeneity into a positive sense of self.